THE WALIMA TRADITION IN THE SULA ISLANDS COMMUNITY IN UMALOYA VILLAGE (SOCIO-CULTURAL ANALYSIS IN THE STRUCTURATION PERSPECTIVE) - Fiki Umalekhoa; Syahrir Ibnu; Jusan Hi. Yusuf (Social Studies and Humanities Journal (SOSHUM), 2025)
Tradition Eitheris one of the local Islamic cultural heritages that still survives strongly in the Sula Islands, North Maluku, especially Yes, in Umaloya Village. This study aims to describe the implementation of the Walima tradition while analyzing the social and cultural values ​​contained within it using a traditional perspective.Anthony Giddens’ structuration theoryThis research uses a qualitative approach with descriptive methods. Data were collected through participant observation, in-depth interviews, and field documentation. The research results show that Walima is not merely a religious ritual, but also a social practice that fosters solidarity, strengthens mutual cooperation, and reinforces the cultural identity of the community. Within the framework of structuration theory, Walima is understood as the result of dialectical reproduction.between agents (community actors) and structures (norms, values, and traditions), which are continuously updated to follow social changes. In addition, Walima functions as a form ofnon-formal social regulationThe traditions that govern social relations in society have a similar power to formal rules in managing social interactions. However, their existence is now faced with the challenges of modernization and changing values ​​among the younger generation. This research emphasizes the need for efforts to preserve local traditions as social capital to strengthen community cohesion amidst the rapid flow of globalization.